SYNTHESIS AND COMPUTATIONAL CALCULATIONS OF NOVEL CHIRAL BIS-1,2,3-TRIAZOLE DERIVATIVES - Gümüş, Ayşegül; Gümüş, Selçuk (MATTER: International Journal of Science and Technology, 2017)
The one-pot synthesis of novel bis-1,2,3-triazole derivatives from homopropargyl alcohol backbones is described. The key intermediates chiral 2-benzothiophenyl (-)-1 and 2-benzofuranyl (-)-2 substituted homopropargyl alcohols are synthesized from their corresponding carboxyaldehyde derivatives by O-propargylation and enzymatic resolution. Enantiomerically enriched homopropargyl alcohol derivatives are reacted with diiodo benzene and sodium azide via one-pot synthesis method and novel chiral bis-benzofuranyltriazole (-)-3 and bis-benzothiophenyltriazole (-)-4 are constructed without isolation of potentially toxic and unstable organic azide intermediates.